Automation of Open VSwitch-Based Virtual Network Configuration Using Ansible on Proxmox Virtual Environment - Marzuki, Khairan; Kholid, Muhammad Idham; Hariyadi, I Putu; Mardedi, Lalu Zazuli Azhar (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Proxmox has a feature that can build a private network in it. Each host on a private network on Proxmox generally shares physical resources, including network connections using a virtual network, one of which is a VLAN. The Proxmox server supports Open VSwitch as a virtual switch. Open virtual switch, an alternative virtual switch quite popular among cloud developers, can be a solution for managing traffic between Virtual Machins and external communications. The method used in this study is the Network Development Life Cycle (NDLC). After applying the automation engine using Ansible, it overcame the problem, namely speeding up configuration and reducing human error or errors in configuring virtual networks. The automation system can speed up the virtual network management process compared to the manual method based on 5 (five) experiments, namely when the manufacturing operation has an average time of 08 minutes and 42 seconds faster. Whereas when the addition operation has an average faster time of 08 minutes 17 seconds. On the other hand, when the deletion operation has an average time of 42 seconds faster.